Purification and sidewall functionalization of multiwalled carbon nanotubes and resulting bioactivity in two macrophage models. (March 2013) - Hamilton, Raymond F.; Xiang, Chengcheng; Li, Ming; Ka, Ibrahima; Yang, Feng; Ma, Dongling; Porter, Dale W.; Wu, Nianqiang; Holian, Andrij
Abstract This study examined the consequences of surface carboxylation of multiwalled carbon nanotubes (MWCNT) on bioactivity. Since commercial raw MWCNT contain impurities that may affect their bioactivity, HCl refluxing was exploited to purify raw "as-received" MWCNT by removing the amorphous carbon layer on the MWCNT surface and reducing the metal impurities (e.g. Ni). The removal of amorphous carbon layer was confirmed by Raman spectroscopy and thermogravimetric analysis. Furthermore, the HCl-purified MWCNT provided more available reaction sites, leading to enhanced sidewall functionalization. The sidewall of HCl-purified MWCNT was further functionalized with the –COOH moiety by HNO3 oxidation. This process resulted in four distinct MWCNT: raw, purified, –COOH-terminated raw MWCNT, and –COOH-terminated purified MWCNT. Freshly isolated alveolar macrophages from C57Bl/6 mice were exposed to these nanomaterials to determine the effects of the surface chemistry on the bioactivity in terms of cell viability and inflammasome activation. Inflammasome activation was confirmed using inhibitors of cathepsin B and Caspase-1. Purification reduced the cell toxicity and inflammasome activation slightly compared to raw MWCNT. In contrast, functionalization of MWCNT with the –COOH group dramatically reduced the cytotoxicity and inflammasome activation. Similar results were seen using THP-1 cells supporting their potential use for high-throughput screening. This study demonstrated that the toxicity and bioactivity of MWCNT were diminished by removal of the Ni contamination and/or addition of –COOH groups to the sidewalls.